Heme Oxygenase-1 and Acute Kidney Injury following Cardiac Surgery - Billings, Frederic T. (S. Karger AG, 2014)
BACKGROUND: Intraoperative hemolysis and inflammation are associated with acute kidney injury (AKI) following cardiac surgery. Plasma-free hemoglobin induces heme oxygenase-1 (HO-1) expression. HO-1 degrades heme but increases in experimental models of AKI. This study tested the hypothesis that plasma HO-1 concentrations are associated with intraoperative hemolysis and are increased in patients that develop AKI following cardiac surgery. METHODS: We measured plasma HO-1, free hemoglobin, and inflammatory markers in 74 patients undergoing cardiopulmonary bypass (CPB). AKI was defined as an increase in serum creatinine concentration of 50% or 0.3 mg/dl within 72 h of surgery. RESULTS: Twenty-eight percent of patients developed AKI. HO-1 concentrations increased from 4.2 ± 0.2 ng/ml at baseline to 6.6 ± 0.5 ng/ml on postoperative day (POD) 1 (p < 0.001). POD1 HO-1 concentrations were 3.1 ng/ml higher (95% CI 1.1-5.1) in AKI patients, as was the change in HO-1 from baseline to POD1 (4.4 ± 1.3 ng/ml in AKI patients vs. 1.5 ± 0.3 ng/ml in no-AKI patients, p = 0.006). HO-1 concentrations remained elevated in AKI patients even after controlling for AKI risk factors and preoperative drug therapy. Peak-free hemoglobin concentrations correlated with peak HO-1 concentrations on POD1 in patients that developed AKI (p = 0.02). Duration of CPB and post-CPB IL-6 and IL-10 concentrations were also associated with increased HO-1 on POD1. CONCLUSION: Plasma HO-1 is increased in patients that develop AKI, and CPB duration, hemolysis, and inflammation are associated with increased HO-1 concentrations following cardiac surgery. Strategies that alter hemolysis and HO-1 expression during cardiac surgery may affect risk for AKI.